2018
DOI: 10.1021/acs.macromol.8b01865
|View full text |Cite
|
Sign up to set email alerts
|

Surface Disentanglement and Slip in a Polymer Melt: A Molecular Dynamics Study

Abstract: We perform nonequilibrium molecular dynamics shear flow simulations of an entangled polymer melt consisting of flexible linear chains. A steady-state rectilinear shear flow is imposed by sliding explicit walls with permanently grafted chains in a planar Couette flow geometry. As the channel average shear rate is increased, a rapid coil−stretch transition of the surface end-grafted chains is observed. The corresponding primitive path network properties are investigated, revealing a disentanglement between surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
(217 reference statements)
2
3
0
Order By: Relevance
“…Our results for a liquid–vapor interface are similar to those reported by Kirk et al for polymers confined by a wall. Those studies demonstrated that the interface has no significant impact on the number of kinks near the interface and that a SLSP model can reproduce these findings accurately.…”
Section: Resultssupporting
confidence: 92%
“…Our results for a liquid–vapor interface are similar to those reported by Kirk et al for polymers confined by a wall. Those studies demonstrated that the interface has no significant impact on the number of kinks near the interface and that a SLSP model can reproduce these findings accurately.…”
Section: Resultssupporting
confidence: 92%
“…Slip has been shown to vary considerably with the applied shear rate, whereas in many cases the variations can be nonmonotonic due to the transition between the weak and the strong flow regimes, and the manifestation of shear-thinning and viscous-heating phenomena. 22,23,61 In situations with strong flow of high molar mass PE chains, the effective slip velocity has been shown 21,22 to rise monotonically with γȧ pp in strong flow situations, in line with the experimental measurements. 12 The simulations by Jabarzadeh et al for C 16 convey a similar picture, wherein slip decreases with increasing γȧ pp in weak flow situations (γė ff /γȧ pp increases), whereas after some point slip increases again (γė ff /γȧ pp decreases) indicating the manifestation of shear-thinning phenomena.…”
Section: Panels C and D Insupporting
confidence: 82%
“…The polymer is subjected to strong flow at . , As shown in Table , the experimental conditions under which the simple shear experiment was performed caused the chains in the system to experience more stretching than chain orientation, as indicated by the magnitude of relative to and reflected by the continuous decrease in surface roughness, R q .…”
Section: Resultsmentioning
confidence: 99%